Mental well-being model of Thai older adults: Comparing the aging in place and aging migrant groups. - Arunya Tuicomepee; Juthatip Wiwattanapantuwong; Panrapee Suttiwan; Rewadee Watakakosol; Sompoch Iamsupasit; Phummaret Phupha (PLoS ONE)
Objective Although aging well and aging in place policies have been encouraged in many countries, a consistent challenge is insufficient evidence on older migrants. This study compared mental well-being models of older adults between aging in place and aging migrant groups. The model included social factors (e.g., social well-being) and personal factors (e.g., cognitive function and psychological distress). Methods Participants were 334 Thais (187 aging in place, 147 aging migrants). Their mean age was 69.79 ± 7.28 years old. All met the selection criteria: age 60 years or over, voluntary participation, and ability to visit the community area for study participation. Instruments were The Modified Mini-Mental State (3MS), 21-item Depression, Anxiety, Stress Scale, 15-item Social Well-Being Scale, and 5-item WHO Well-being Index. Data were collected in the five regions of Thailand from March 2021 to February 2022. Local psychologists and research assistants assessed and interviewed the participants. Maximum likelihood with the Satorra-Bentler correction was used for parameter estimation. Results Both models fit the empirical data. The multi-group model estimation yielded a difference between the models. The factors of the aging in place group that were associated with mental well-being were psychological distress (SE = 0.08, p < .001) and cognitive function (SE = 0.07, p < .001), but not social well-being (SE = 0.09, ns). For the migrant group, psychological distress (SE = 0.12, p < .01) and social well-being (SE = 0.11, p < .001) were significant predictors of mental well-being, but not of cognitive function (SE = 0.12, ns). Conclusions By understanding differences in the mental well-being models between the two groups, policy makers and service providers can better address the needs of older adults. Policies and programs should be designed to reduce their psychological distress. Maintaining social connections can be crucial for migrants, while activities such as lifelong learning and physical activities to enhance cognitive function can benefit people who are aging in place.